Effect of templates on the synthesis of organized mesoporous alumina - Ramli, Zainab; Chandren, Sheela (Malaysian Society of Analytical Sciences, 2007)

(untitled)
Organized mesoporous materials represent a class of molecular sieves because of its high potential for commercial applications in adsorption and catalysis. In this study, organized mesoporous alumina was synthesized by the sol-gel method using various organic templates, i.e. cationic, neutral and anionic surfactants. Surface porosity of the synthesized aluminas obtained exhibit materials in the mesopore ranges. The morphology of the samples consists of wormhole-like mesostructure in the nano-region (20 – 70 nm). Sample with cetyl trimethylammonium bromide as cationic templates has the narrowest pore distribution centred at 8 nm as compared to samples synthesized with Triton X-114 (neutral) and stearic acid (anionic). All samples showed only Lewis acidity. Acidity and mesoporous character present in these mesoporous alumina samples showed that this material has potential as catalyst support and also used in Lewis acid catalyzed reactions. Study showed that the cationic surfactant is a better template to obtain uniform mesoporous alumina that might be due to the weak interaction between the template and the surface of the alumina.